Laguardia (2018) ebook - Okorafor, Nnedi (LaGuardia (2018)., 2022)
Deluxe edition of the Hugo and Eisner Award-winning graphic novel! Exclusive extras include a chapter of Okorafor's script, a new cover and never-before-seen art from Ford, a behind-the-scenes look at the creation process, an extensive process art section, and more! On a planet Earth bursting with integrated extraterrestrial life, pregnant doctor Future Nwafor Chukwuebuka is fleeing Nigeria under mysterious conditions. Her fiance doesn't know she's left, and she's smuggling an illegal, sentient plant into NYC. There, she'll be thrown into a vibrant immigrant community of humans and aliens, fighting for social justice and facing her past and her unexpected future. ""The best of Okorafor's prose‚Äîpersonal, political and deeply relatable."" ‚ÄìNewsarama